EFEKTIVITAS KIE (KOMUNIKASI, INFORMASI DAN EDUKASI) TERHADAP PENGGUNAAN KB IUD (INTRA UTERINE DEVICES) DI WILAYAH KERJA PUSKESMAS TANJUNG REJO KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Sri Suharti (Jurnal Ilmiah Kebidanan Imelda, 2016)
The use of IUD contraceptive in the working area of Puskesmas Tanjung Rejo in 2012 was only 6.45%. One of the factors causing the Family Planning acceptors are less interested in using IUD contraceptive is the factor of communication, information and education (transparency, empathy, supporting attitude, positive attitude, and equality) of the health workers to the FP acceptors. The purpose of this explanatory study was to analyze the effectiveness of the communication, information and education (transparency, empathy, supporting attitude, positive attitude, and equality) of the health workers on the use of IUD contraceptive in the working area of Puskesmas Tanjung Rejo, Deli Serdang District. The population of this study was all of the 7164 mothers using contraceptives in the working area of Puskesmas Tanjung Rejo, Deli Serdang District, and 132 of them were selected to be the samples for this study through simple random sampling technique. The data for this study were obtained through questionnaire-based interviews. The data obtained were analyzed through multiple logistic regression tests at α = 5%. The result of this study statistically showed that the factors of transparency, empathy, supporting attitude, and positive attitude had influence on the use of IUD contraceptive and the factors of support, positive attitude and occupation did not have influence on the use of IUD contraceptive in the working area of Puskesmas Tanjung Rejo, Deli Serdang District. The most dominant variables having influence on the use of IUD contraceptive in the working area of Puskesmas Tanjung Rejo, Deli Serdang District were age, education, parity, transparency, empathy, equality, and media. These seven variables had influence on the use of IUD contraceptive for 59.4% meaning that the remaining 41.1% was influenced by the other factors which were not included in this study. The health workers are suggested to improve their communication, information and education on IUD contraceptive and to increase the coverage of the use of IUD contraceptive by inviting the FP acceptors to attend the extension and the health workers especially those working in the working area of Puskesmas Tanjung Rejo, Deli Serdang District are suggested to more actively provide the communication, information and education activity on IUD contraceptive to the FP acceptors.